Strategi Pengembangan Wilayah Pesisir Di Provinsi Bengkulu - Anzori Tawakal; As’ad Hasan (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2019)
As one of the coastal areas, Bengkulu Province has very potential natural wealth. Even so, the development has not run optimally, where the level of community welfare is still low and development is still lagging behind. This study aims to identify the strategy for developing coastal areas in Bengkulu Province using SWOT analysis. The results of the study found that the strategy for developing the coastal region of Bengkulu province could be done using an aggressive strategy, which illustrates that the situation is very good because there are forces that are utilized to seize profitable opportunities, to overcome various weaknesses and threats. The development strategy of the coastal region of Bengkulu province can be done by optimally utilizing coastal and marine natural resources to be carried out to meet the broad share of the share of domestic and foreign fishery products, enforce existing legislation to increase the level of domestic fish consumption, acceleration of government policies to accelerate the development of marine and fisheries in order to provide raw materials for processed and fishery products, strengthen permanent government institutions to meet the demand for processed marine and fishery products, increase the allocation of funds managed by the government to increase product competitiveness and prices of marine products , increasing the development of infrastructure/facilities, advances in marine and fisheries technology in developing maritime tourism and tourism as well as increasing foreign and domestic investment.